Postoperative Complications in the Early Phase Following Laparotomy and Ileostomy for Ileal Perforation - Imam Alam; Mujahid ur Rehman; Anam Shah; Shah Nawaz Khatti; Irshad Ahmed; Kamran Hyder Abbasi (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Objective: To explore the early postoperative challenges faced by 100 patients undergoing laparotomy and ileostomy for ileal perforation. Study Design: A prospective study Duration and place of study: this study was conducted in Mekran Medical College Kech Turbat Pakistan from January 2024 to January 2025 Methodology: The present study is a descriptive study. We enrolled 100 consecutive adult patients diagnosed with peritonitis secondary to ileal perforation. Following general anesthesia, all underwent midline laparotomy with loop ileostomy formation. Patients were monitored for stoma-related and general postoperative complications. Outcomes were assessed at two weeks post-surgery. Results: Just over half of the cohort (52%) experienced at least one ileostomy-related complication. Wound infection topped the list (n=20; 20%), closely followed by peristomal skin excoriation (n=15; 15%). Wound dehiscence occurred in 12 patients (12%), and stoma retraction in 7 (7%). Notably, stoma-related fluid losses led to electrolyte imbalances in 18% (n=18), contributing to additional morbidity. No mortalities were recorded within the two-week follow-up. Conclusions: More than half of patients with ileal perforation managed by laparotomy and ileostomy face stoma-specific complications early in their recovery, with wound infection and fluid-loss–related electrolyte disturbances being most prevalent. Vigilant stoma care and proactive fluid-electrolyte management are critical to reducing these burdens and improving short-term outcomes.